STRETCH (Students Ready To Make Change): Making a Difference in the Lives of Students - Lukowiak, Twila; Ghareeb, James; Wadi, Sarah; Stanis, Samantha; Walter, Jack (Journal of the American Academy of Special Education Professionals, 2017)
Described in this multifaceted article are various types of bullying and the potential long-term, harmful effects. The authors also depict a multitude of strategies for parents / guardians and teachers in assisting children who have suffered from bullying. Furthermore, the authors share their personal experiences with bullying and explain the reasons they are extremely passionate and dedicated in doing whatever is in their power to end bullying. Finally, a university student organization named STRETCH (Students Ready To Make Change) is introduced. Members of STRETCH create multi-media presentations to assist students in understanding the harms of bullying and the benefits of performing acts of kindness for all individuals. STRETCH members perform these entertaining presentations which consist of videos, personal stories, music, and educational activities to K-12 students in an effort to make a difference in their lives and letting them know they are not alone.